Potential and Obstacles of Character Education In Elementary Schools - Safari, Shabina Meisya Adriani; Hunafa, Reza; Maulani, Galih Abdul Fatah; Hamdani, Nizar Alam (Indonesian Journal of Community Empowerment (IJCE), 2024)
This research aims to describe the implementation of character education at SDN 01 Girimakmur Malangbong and the obstacles faced by teachers in implementing it. character education at SDN 01 Girimakmur Malangbong. This research is a qualitative descriptive research. The data collection technique used is observation, interviews and documentation. The main instrument is the researcher using tools help with interview guidelines and observation guidelines. Analysis procedures in this researchare: Data reduction, data presentation, and verification/drawing conclusions. Results This research shows that the form of implementing character education at SDN 01 Girimakmur Malangbong. manifested in integration in self-development programs, integration in learning activities, as well as character values ​​developed by the school. Integration in the self-development program consists of routine activities, role modeling, spontaneous activities and conditioning. Character values ​​developed at SDN 01 Girimakmur Malangbong. namely religious values, honesty, discipline, responsibility and friendship.